VD_FINDINFO HC / 2011 / 457 vom 17. August 2011 - VD Tribunal cantonal (2011)
BAIL À LOYER, LOCAL PROFESSIONNEL, CONGÉ-PRESSION | 271 al. 1 CO, 271 CO, 271a al. 1 CO, 271a al. 1 let. b CO, 271a CO, 444 al. 1 ch. 3 CPC, 444 CPC, 470 al. 1 CPC, 470 CPC